2023
DOI: 10.1021/acs.est.3c05694
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation on the Mechanism for Algae Inactivation by the Ultraviolet/Peracetic Acid Process: Role of Reactive Species and Performance in Natural Water

Lisan Cao,
Zongping Wang,
Yujie Cheng
et al.

Abstract: This study provided an in-depth understanding of enhanced algae inactivation by combining ultraviolet and peracetic acid (UV/PAA) and selecting Microcystis aeruginosa as the target algae species. The electron paramagnetic resonance (EPR) tests and scavenging experiments provided direct evidence on the formed reactive species (RSs) and indicated the dominant role of RSs including singlet oxygen (1O2) and hydroxyl (HO•) and organic (RO•) radicals in algae inactivation. Based on the algae inactivation kinetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nevertheless, PAA alone could only directly degrade certain organic contaminants with electron-rich structures (e.g., sulfur moiety, aromatic ring, and CC bond) . Up to now, a number of activation strategies have been proposed to enhance the oxidative performance of PAA, such as energy input (e.g., ultraviolet, , heat, electrochemistry, microwave, and ultrasound), metal catalysts (e.g., homogeneous and heterogeneous transition metals), carbon materials, , and anionic catalysts (e.g., phosphate, bromide, , iodine, , chloride, and nitrite), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PAA alone could only directly degrade certain organic contaminants with electron-rich structures (e.g., sulfur moiety, aromatic ring, and CC bond) . Up to now, a number of activation strategies have been proposed to enhance the oxidative performance of PAA, such as energy input (e.g., ultraviolet, , heat, electrochemistry, microwave, and ultrasound), metal catalysts (e.g., homogeneous and heterogeneous transition metals), carbon materials, , and anionic catalysts (e.g., phosphate, bromide, , iodine, , chloride, and nitrite), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The quenching method is commonly used to assess the maximum contribution of a specified reactive species by adding an excessive amount of quencher to induce inhibition. This method has gained popularity due to its simplicity and convenience, finding successful applications in various fields. However, our previous research on the quenching of singlet oxygen ( 1 O 2 ) has revealed that multiple relationships exist between the quenching effect and the contribution of reactive species, rather than simple inhibition indicating contribution . Additionally, other studies also pointed out that quenchers may alter the production conditions or mechanisms of reactive species, , potentially leading to evaluation errors.…”
Section: Introductionmentioning
confidence: 99%